Jews of Kurdistan and the Doctrinal Origins of the Jews of the City of Zakho - Ahmed, Khatab I.; Yousif, Tawfeeq R. (Humanities Journal of University of Zakho, 2017)
The research cares to study the history of Jews existence in Kurdistan in general , and studying the doctrine origin of Zakho Jews people particular, through returning to the source and reference specialized in this subject whether old or new, where through making comparisons between the religious activities of Zakho Jews people and other Jews people especially the three main sect (Samarian, Rabbincall, Karaism ) , it shows that the Jews of Zakho have practiced some religious ritual very similar to what the Samarian sect practiced rather than the two other sects rabbincall, Karaism, it is preferred largely that the Jews of Zakho belong in their historical and doctrine origins to the Samarian sect and what emphasized this view is that Benjamin of Tudela one of the Jewish traveler from Rabbincall sect , who visited Kurdistan in 600 A.H – 1200 A.D. he mentioned that the Jews of al Amadian city are belong to the ten remaining tribes of Assyrian captivity, who have been brought from Nablus, so it may be inferred that the Jews of Kurdistan in general are from the Samarian Jews, there is also some kind of similarity between the religious ritual of the two sects Samarian and Karaism, while the rabbincall sects is different from both two sects, where it was not noticed any existence of Jews that belong to these two sects in the Zakho.